2018
DOI: 10.3389/fphys.2018.00899
|View full text |Cite
|
Sign up to set email alerts
|

Eplerenone Reverses Cardiac Fibrosis via the Suppression of Tregs by Inhibition of Kv1.3 Channel

Abstract: Background: Fibroblast proliferation is a critical feature during heart failure development. Previous studies reported regulatory T-lymphocytes (Tregs)’ protective role against myocardial fibrosis. However, notably, Tregs also secrete fibrogenic cytokine TGF-β when activated. This study aimed to clarify the intriguing link between Tregs and fibrosis, the role of Tregs Kv1.3 potassium channel (regulating T-lymphocytes activation) in the fibrosis process, and how selective aldosterone receptor antagonist Epleren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Shao et al showed that MR modulates the activation of Treg cells in congestive heart failure. 106 Advanced congestive heart failure activates Treg cell proliferation via the upregulation of Kv1.3 K + channel, which promotes cardiac fibrosis by stimulating secretion of TGF-β. Coincubation of cardiac fibroblasts with Treg cells increased proliferation and levels of collagen I, III, and matrix metalloproteinase (MMP)-2.…”
Section: Aldosterone and Adaptive Immunitymentioning
confidence: 99%
“…Shao et al showed that MR modulates the activation of Treg cells in congestive heart failure. 106 Advanced congestive heart failure activates Treg cell proliferation via the upregulation of Kv1.3 K + channel, which promotes cardiac fibrosis by stimulating secretion of TGF-β. Coincubation of cardiac fibroblasts with Treg cells increased proliferation and levels of collagen I, III, and matrix metalloproteinase (MMP)-2.…”
Section: Aldosterone and Adaptive Immunitymentioning
confidence: 99%
“…Similarly to their helper CD4 + counterpart, human T reg s also have a high number of voltage-gated K V 1.3 channels ( Estes et al, 2008 ; Shao et al, 2018 ) and a low number of K Ca 3.1 channels in their membrane ( Varga et al, 2009 ). Intratumoral T reg s have a peculiar T-cell receptor repertoire whose stimulation may have an important role in their immunosuppressive function ( Ahmadzadeh et al, 2019 ).…”
Section: Immunity and Pdacmentioning
confidence: 99%
“…Comparative expression analysis revealed that Tregs of MS patients express fewer Kv1.3 channels than naive cells, while this difference was not found in healthy donors [43]. Accordingly, modulation of Kv1.3 supports a protective channel function: upregulation resulted in boosted Treg proliferation, and experiments with the high-affinity Kv1.3 antagonist eplerenone revealed diminished TGF-β and IL-10 secretion in treated Tregs [44]. Furthermore, inhibition of Kv1.3 in human lymphocytes led to decreased Ca 2+ entry with larger defects monitored in CD4 + than CD8 + T cells [45].…”
Section: Crac Channelsmentioning
confidence: 91%